Culture, migration, and health communication in a global context - Mao, Yuping (Assistant professor of communication studies); Ahmed, Rukhsana (Routledge research in health communication ;, 2017)
"Both international and internal migration brings new challenges to public health systems. This book aims to critically review theoretical frameworks and literature, as well as discuss new practices and lessons related to culture, migration, and health communication in different countries. It features research and applied projects conducted by scholars from various disciplines including media and communication, public health, medicine, and nursing. "- Resumé vydavatel